Euglycaemic diabetic ketoacidosis in bariatric surgery patients with type 2 diabetes taking canagliflozin. (20th August 2018) - van Niekerk, Christoffel; Wallace, James; Takata, Mark; Yu, Roger
Abstract : A 52-year-old type 2 diabetic man previously on canagliflozin developed severe anion gap metabolic acidosis and markedly elevated beta-hydroxybutyrate on postoperative day (POD) 2 status post laparoscopic Roux-en-Y gastric bypass. An insulin drip and aggressive intravenous fluid repletion were initiated, and electrolytes were monitored and repleted. His anion gap closed, and he was discharged on POD 4. This euglycaemic diabetic ketoacidosis prolonged his hospital stay by 2 days.